Impact of future HERA data on the proton PDF uncertainties using the ZEUS NLO QCD fit - Gwenlan, C; Cooper-Sarkar, A; Targett-Adams, C (IOP Publishing, 2006)
The high precision and large kinematic coverage of the data from the HERA-I running period (1994-2000) have already allowed precise extractions of proton parton distribution functions. The HERA-II program is now underway and is expected to provide a substantial increase in the luminosity collected at HERA. In this paper, the first estimate of the impact of future data from HERA, on the proton PDF uncertainties, is presented. Next-to-leading order QCD predictions for inclusive jet cross sections at the LHC are presented using the projected PDFs.